2011
DOI: 10.1177/0333102411422383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cortical spreading depression on basal and evoked traffic in the trigeminovascular sensory system

Abstract: These results suggest that there is a continuous baseline traffic in primary trigeminovascular fibres and that CSD does not act to increase this traffic by a peripheral action alone - rather, it must produce some of its effect by a mechanism intrinsic to the central nervous system. Thus the pain of migraine may not always be the result of peripheral sensory stimulation, but may also arise by a central mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 73 publications
2
65
1
Order By: Relevance
“…Studies performed with human neocortical sections showed that even a single CSD event could facilitate excitatory post-synaptic potentials and elicit long-term potentiation, thus contributing to cortical hyperexcitability (53). CSD may also generate headache by activating central trigeminovascular neurons through subcortical pathways that result in disinhibition of sensory neurons within the TNC (54). Meningeal plasma extravasation has been detected by photon-emission tomography during migraine (55).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with human neocortical sections showed that even a single CSD event could facilitate excitatory post-synaptic potentials and elicit long-term potentiation, thus contributing to cortical hyperexcitability (53). CSD may also generate headache by activating central trigeminovascular neurons through subcortical pathways that result in disinhibition of sensory neurons within the TNC (54). Meningeal plasma extravasation has been detected by photon-emission tomography during migraine (55).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these new data, that could also explain the reasons for the previous study negative findings, the crucial role of CSD as a sufficient migraine pain trigger, at least in MA, has been fully rehabilitated [31]. However, the assumption that CSD-dependent peripheral trigeminovascular activation is the main pathway involved in the second-order trigeminal neurons activation has been challenged by a very interesting work by Lambert et al [32]. The direct recording of trigeminal nuclei neurons involved in meningeal pain processing following CSD induction showed only minor differences in firing pattern before versus after the peripheral exclusion of trigeminal input by lignocaine injection in Gasser ganglion, confirming that CSD could directly modulate the trigeminal nuclei activity.…”
Section: New Evidences On the Cortical Spreading Depression Role In Mmentioning
confidence: 89%
“…A dense network of dural nerve fibres that react with substance P and calcitonin gene-related peptide (CGRP) has been found [12], the role of the latter in the development of new treatments is discussed further in this review. CSD has also been reported to cause changes in brainstem nociceptive neuronal activity even when the trigeminal pathway has been inhibited [13]. In humans, functional imaging has shown changes in cortical function and blood flow and the patterns of spread are suggestive of CSD [10].…”
Section: Pathophysiology Of Migrainementioning
confidence: 99%